2017
DOI: 10.1017/s003118201700213x
|View full text |Cite
|
Sign up to set email alerts
|

Monophyly of the species of Hepatozoon (Adeleorina: Hepatozoidae) parasitizing (African) anurans, with the description of three new species from hyperoliid frogs in South Africa

Abstract: Haemogregarines (Apicomplexa: Adeleiorina) are a diverse group of haemoparasites reported from almost all vertebrate classes. The most commonly recorded haemogregarines to parasitize anurans are species of Hepatozoon Miller, 1908. To date 16 Hepatozoon species have been described from anurans in Africa, with only a single species, Hepatozoon hyperolli (Hoare, 1932), infecting a member of the Hyperoliidae. Furthermore, only two Hepatozoon species are known from South African anurans, namely Hepatozoon theileri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
(86 reference statements)
0
21
1
Order By: Relevance
“…Prior to the 21st century, classification of species of Hepatozoon was based on their life history, host identity and morphological characteristics. However, with recent advances in molecular techniques, phylogenetic analyses on the relationships between species have become possible [13][14][15][16]. Morphological characteristics used to distinguish between species of Hepatozoon include gamont and nucleus dimensions; position of the nucleus within the gamont; number and arrangement of vacuoles and staining properties [17,18], as well as characteristics of other developmental stages [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the 21st century, classification of species of Hepatozoon was based on their life history, host identity and morphological characteristics. However, with recent advances in molecular techniques, phylogenetic analyses on the relationships between species have become possible [13][14][15][16]. Morphological characteristics used to distinguish between species of Hepatozoon include gamont and nucleus dimensions; position of the nucleus within the gamont; number and arrangement of vacuoles and staining properties [17,18], as well as characteristics of other developmental stages [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to constant improvement of molecular techniques, the number of studies on haemogregarines has systematically increased, with several studies relying solely on these methods to detect species of Hepatozoon in their hosts [11,[28][29][30][31][32]. Recent research has shown that a difference in p-distance of between 1-2% of the 18S rRNA gene is sufficient to distinguish between species of haemogregarines if supported by morphological data [16,18,33,34]. Other studies, such as Metzger et al [35], incorporate both molecular and some degree of morphological investigations, showing the importance of utilizing a more holistic approach when distinguishing among species of Hepatozoon.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) used the pair of primers HepF300 and HepR900 (Ujvari et al ., 2004) to amplify a 600 bp fragment of the 18S rRNA. In the current work we tested two other primers, which combined with the previous pair produced an amplicon of around 1700 bp, the majority of the 18S rRNA (Netherlands et al ., 2018). The set of primers HAMF (Criado-Fornelio et al ., 2006) and HepF300 produced a 900 bp fragment, providing 300 extra bases to the 5â€Č end of the 600 bp fragment previously obtained, while 2868 (Medlin et al ., 1988) and HepR900 amplified a 1400 bp product, adding 800 bp to the 3â€Č end of the previous fragment.…”
Section: Methodsmentioning
confidence: 99%
“…Conditions for PCR of both fragments were as follows: initial denaturation at 95 °C for 3 min, followed by 35 cycles, entailing a 95 °C denaturation for 30 s, annealing at 61 °C for 30 s with an end extension at 72 °C for 2 min, and following the cycles a final extension of 72 °C for 10 min (Netherlands et al 2018).…”
Section: Dna Extraction Pcr and Phylogenetic Analysis Of 18s Rdnamentioning
confidence: 99%